2015
DOI: 10.1016/j.cej.2015.06.076
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement effects of chelating agents on the degradation of tetrachloroethene in Fe(III) catalyzed percarbonate system

Abstract: The performance of Fe(III)-based catalyzed sodium percarbonate (SPC) for stimulating the oxidation of tetrachloroethene (PCE) for groundwater remediation applications was investigated. The chelating agents citric acid monohydrate (CIT), oxalic acid (OA), and Glutamic acid (Glu) significantly enhanced the degradation of PCE. Conversely, ethylenediaminetetraacetic acid (EDTA) had a negative impact on PCE degradation, which may due to its strong Fe chelation and HO• scavenging abilities. However, excessive SPC or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 39 publications
2
18
0
2
Order By: Relevance
“…For example, the magnitude of PCE degradation in 5 min increased from approximately 4% to 98%, 53%, 59% and 10% for the HAH, SS, ASC and SA reagents, respectively. The much slower rate of degradation observed for the control is consistent with the results of previous research [29], which demonstrated that more than 30 min was required for the complete degradation of PCE in the Fe(III)/SPC system in the absence of reducing agents, even when high concentrations (10 mM) of Fe(III) and SPC were used.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For example, the magnitude of PCE degradation in 5 min increased from approximately 4% to 98%, 53%, 59% and 10% for the HAH, SS, ASC and SA reagents, respectively. The much slower rate of degradation observed for the control is consistent with the results of previous research [29], which demonstrated that more than 30 min was required for the complete degradation of PCE in the Fe(III)/SPC system in the absence of reducing agents, even when high concentrations (10 mM) of Fe(III) and SPC were used.…”
Section: Resultssupporting
confidence: 90%
“…S1 in Appendix A. Supplementary data) [29] and Fe(II) catalyzed SPC systems [19] can degrade PCE effectively. However, the degradation rate is significantly different because of different PCE degradation pathways as well as the different concentrations of Fe(II) present.…”
Section: Resultsmentioning
confidence: 99%
“…The Fe(III)-activated CaO 2 exhibited several limitations, such as precipitation of the iron as ferric hydroxide (Fe(OH) 3 ), which does not readily redissolve and inhibits the oxidation process 41 . The addition of chelating agents such as citric acid, tartaric acid, oxalic acid, and glutamic acid has been proposed as a way to overcome these drawbacks 41 , 42 . We believe that the caffeic acid and chlorogenic acid present in coffee grounds probably contributed to the Fenton process by reducing Fe 3+ to Fe 2+ and/or served as electron donors binding Fe 2+ to maintain the activity of Fe in the reduced state in the Fenton cycle.…”
Section: Discussionmentioning
confidence: 99%
“…O principal composto usado para a ativação do PCS é o ferro, na forma bi ou trivalente. O ferro (II) é o mais comum em testes de degradação de contaminantes orgânicos, porém, o uso do ferro (III) vem ganhando um destaque em alguns estudos (MIAO et al 2015c;FU et al 2016aFU et al , b, 2017aCUI et al 2017).…”
Section: Propriedades Físico-químicasunclassified
“…Desta forma, a eficiência do sistema oxidativo poderá ser mantida (MIAO et al 2015b. No entanto, altas concentrações de peróxido de hidrogênio (> 20 mmol L -1 ) podem promover um auto-consumo do radical hidroxila (Equação 24) (SILVA et al 2011) e consumo do radical hidroxila por reação com o peróxido de hidrogênio, produzindo o radical hidroperoxila (Equação 25) (MIAO et al 2015c). A tabela 3 sumariza algumas das vantagens e desvantagens do uso dos sistemas catalisados por Fe(II) e Fe(III).…”
Section: Ativação Por Ferro (Iii)unclassified